Influência de alguns elementos meteorológicos sobre a ocorrência de casos de depressão em pacientes do Hospital de Clínicas (Gaspar Viana) - VIEIRA, Luciana Cristina de Sousa (2019)
With the objective to present the importance of the weather in the psychological state of people, a study was made through in which was verified of what forms the changes of the seasons of the year can be related the alterations in the human behavior. The study evidenced that some people present a bigger or lesser degree of changes in some of its common habits, these changes reflect in sleep, appetite, energy, mood, and in some cases, it becomes necessary the search for a health professional (psychiatrist). The causes of this kind of depression are still little known, but exist possibility that they might be related to the reduction of natural light and the high values of temperature found in this region located next to meteorological equator. The analyses were made throughout using data from “Caspar Viana Clinics Hospital”, in Belém - Pará and from National Institute of Meteorology 2°DISME (INMET), besides bibliographical research. Its was evidenced that, approximately, four women for each man have greater change in the psicosocial behavior, and greater incidence between the twenty and forty years, but can occur in all ages, also in infancy. It has possibility to exist genetic predisposition. People with familiar description of depression have greater probability to suffer sazonal depression.